Influence of different sources and concentrations of flavors on the intake in caprine - Vargas-Rodríguez, Claudio Fabián (2018)
The behavior of caprine to taste stimuli affects the consumption of dry matter (MS), and the inclusion of sensorial stimulators can increase productivity. The objective of this experiment was to evaluate different sources and concentrations of flavoring on forage intake in goats. The research was developed at the Dairy Cattle Experimental Station “Alfredo Volio Mata” of the University of Costa Rica, in Ochomogo, Cartago, Costa Rica during October 2015. A coffee-shop test was used in a block crossover model. Pennisetum purpureum cv King grass mixed with four flavors (acid, bitter, sweet and salty) in five different concentrations (0, 0.25, 0.5, 0.75 and 1.0%) was supplied to a group of goats. Goats showed the greater preference for forage mixed with a bitter flavor, and less preference for sweet and salty flavors. The forage intake on a dry basis showed by the animals when the acid flavor was applied, was 0.977 kg/d, when the sweet and salty flavorings were used the intake was 0.855 and 0.822 kg/d, respectively. These differences were significant. The goats consumed 68.28% of the amount of offered forage when the bitter flavor was used, but only consumed 56.43% of what was offered when the forage was acidified. When comparing the inclusion of any flavor with respect to an unflavored control treatment, no significant differences were observed in the consumption of dry matter or the degree of acceptance. No effect on dry matter consumption or acceptance percentage was observed when different concentrations of flavorings were used. The interaction between flavor and flavor concentration did not generate significant differences in any of the evaluated parameters.